2014
DOI: 10.4238/2014.february.19.10
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of novel EST-SSRs in the showy dendrobium, Dendrobium nobile (Orchidaceae)

Abstract: ABSTRACT. Expressed sequence tag (EST)-derived simple sequence repeat (SSR) markers could enrich the current resource of molecular markers. In this study, microsatellite markers were developed for Dendrobium nobile Lindl. by mining the ESTs. Twenty-eight ESTSSRs amplified 2 to 6 nucleotide repeats with a mean number of 2.82 alleles per locus. The observed and expected heterozygosities per locus ranged from 0.158 to 0.579 and 0.422 to 0.752, respectively. These novel EST-SSRs enriched the current resource of mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…According to the previous research of our group 36 and the present data analysis, the contents of SGs from D. nobile may be correlated with altitude. To visualize our findings, we performed HCA on six SGs from D. nobile grown in different environments.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…According to the previous research of our group 36 and the present data analysis, the contents of SGs from D. nobile may be correlated with altitude. To visualize our findings, we performed HCA on six SGs from D. nobile grown in different environments.…”
Section: Resultssupporting
confidence: 73%
“…According to the previous research of our group 36 At present, studies have shown that the accumulation of secondary metabolites is closely related to the environment. 37 Different attachment methods (rock wall, pear tree, greenhouse potted plant) affect the secondary metabolite contents of D. officinale.…”
Section: Hierarchical Cluster Analysismentioning
confidence: 92%
“…The genetic diversity, including the means of the observed ( Ho ) and expected heterozygosity ( He ) (Table 4), of G. flabilabella was low compared with that of other Orchidaceae species, such as Dendrobium huoshanense (0.512 and 0.569) (Wang et al [2012b]), Dendrobium officinale (0.720 and 0.740) (Xie et al [2010]), Dendrobium officinale (0.514 for Ho ) (Lu et al [2012]), and Dendrobium nobile (0.350 and 0.608) (Lu et al [2014]). Unfortunately, no data for any Gastrodia taxa or mycoheterotrophic orchids are available for the comparison of genetic variability.…”
Section: Resultsmentioning
confidence: 99%
“…Simple sequence repeat (SSR) markers have been used for germplasm management and marker-assisted selection of plants because of their advantages of being highly polymorphic, highly reproducible, and readily transferable to other populations within the same species and related species and genera (Kang et al 2015;Lu et al 2013;Tsai et al 2015). Recently, a more informative co-dominant type of marker (i.e., SSRs) has been developed to identify Dendrobium and genetic linkage maps of Dendrobium (Liu et al 2014;Lu et al 2012a;Lu et al 2012b;Lu et al 2014. However, these studies were most focused on medical Dendrobium and Nobile-type Dendrobium plants.…”
mentioning
confidence: 99%